2011
DOI: 10.1074/jbc.m111.240044
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Catch Bonds by Rate of Force Application

Abstract: The current paradigm for receptor-ligand dissociation kinetics assumes off-rates as functions of instantaneous force without impact from its prior history. This a priori assumption is the foundation for predicting dissociation from a given initial state using kinetic equations. Here we have invalidated this assumption by demonstrating the impact of force history with singlebond kinetic experiments involving selectins and their ligands that mediate leukocyte tethering and rolling on vascular surfaces during inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 50 publications
1
45
2
Order By: Relevance
“…Because the WT cadherins were loaded at a constant ramp rate to a constant hold force, we also tested the ramp-rate dependence of ideal bond formation; a recent study has shown that a mechanical bond that behaves as a catch-slip bond at low ramp rates may transform to slip-only bonds at high ramp rates (35). When we increased the ramp rate by an order of magnitude, the WT cadherins with 0.3 s interaction time continued to behave as ideal bonds, indicating the rate of force application did not affect ideal bond behavior (SI Appendix, Fig.…”
Section: Ideal Bonds Are Measured When Wt Cadherins Interact For a Shortmentioning
confidence: 99%
“…Because the WT cadherins were loaded at a constant ramp rate to a constant hold force, we also tested the ramp-rate dependence of ideal bond formation; a recent study has shown that a mechanical bond that behaves as a catch-slip bond at low ramp rates may transform to slip-only bonds at high ramp rates (35). When we increased the ramp rate by an order of magnitude, the WT cadherins with 0.3 s interaction time continued to behave as ideal bonds, indicating the rate of force application did not affect ideal bond behavior (SI Appendix, Fig.…”
Section: Ideal Bonds Are Measured When Wt Cadherins Interact For a Shortmentioning
confidence: 99%
“…It is also a challenge to develop a hierarchical organization of DE-based sensors and actuators that can respond to external stimuli in a programmable and intelligent way. Modeling such hierarchical compartmentalization generally requires theories of large deformation strongly coupled to other fields such as electronics, as well as microscopic processes such as bonding kinetics (Sarangapani et al, 2011;Ju et al, 2015) and mass transport (Jiang et al, 2015) that ubiquitously occur within materials and at interfaces. The analytical and numerical approach based on continuum mechanics and thermodynamics will continue to play an enormous role in understanding these materials, and in modeling these structures and designing these devices (Chen, 2014), and the bottom-up investigation of the microscopic processes in response to external stimuli has just begun.…”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%
“…This counterintuitive behavior-a bond is strengthened by applying a force to it-is no longer a theoretical curiosity but has, in recent years, been experimentally demonstrated in a range of noncovalent biophysical bonds where it has become widely known as a catch bond [4,6]. For protein-protein bonds, such behavior is generally ascribed to specific conformational properties of the molecules involved [7][8][9][10][11]; we will show that catch bond behavior is generic for protein complexes in which multiple pathways for dissociation exists. In this paper, we will define a catch bond to mean a bound state whose average lifetime Ď„ (f ) possesses an initial regime of increase with force:…”
Section: Introductionmentioning
confidence: 99%